Caracterización del sistema de reguladores LuxR solos de Arthrobacter sp. UMCV2 como moduladores de la respuesta de la bacteria a su compuesto N, N-dimetilhexadecilamina - Chávez Moctezuma, Martha Patricia (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
Quorum sensing (QS) is a bacterial cell-cell communication system with genetically regulated mechanisms dependent on cell density. Canonical QS systems in Gram-negative bacteria possess an autoinducer synthase (LuxI family) and a transcriptional regulator (LuxR family) that respond to an autoinducer molecule. In Gram-positive bacteria, the LuxR transcriptional regulators solos (not associated with a LuxI homolog) may play key roles in intracellular communication. Arthrobacter sp. UMCV2 is an actinobacterium that promotes plant growth by emitting the volatile organic compound N, N-dimethylhexadecylamine (DMHDA). This compound induces iron deficiency, plant defense responses, and Arthrobacter sp. UMCV2 swarming motility. In this study, the draft genome of this bacterium was assembled and compared with the genomes of type strains of the Arthrobacter genus, finding that it does not belong to any previously described species. Genome explorations also revealed the presence of 16 luxR-related genes, but no luxI homologs were discovered. Eleven of these sequences possessed the LuxR characteristic DNA-binding domain with a helix-turn-helix motif and were designated as auto-inducer-related regulators (AirR). Four sequences possessed LuxR analogous domains and were designated as auto-inducer analogous regulators (AiaR). When swarming motility was induced with DMHDA, eight airR genes and two aiaR genes were upregulated. These results indicate that the expression of multiple luxR-related genes is induced in actinobacteria, such as Arthrobacter sp. UMCV2, by the action of the bacterial biocompound DMHDA when QS behavior is produced.

El quorum sensing (QS) o percepción de quorum, es un sistema bacteriano de comunicación célula-célula el cual regula genéticamente mecanismos dependientes de la densidad celular. Los sistemas canónicos QS en bacterias Gram-negativas poseen una sintasa autoinductor (familia LuxI) y un regulador transcripcional (familia LuxR) que responde a una molécula autoinductora. En bacterias Gram-positivas, los reguladores transcripcionales LuxR solos (que no están asociados con un homólogo LuxI) pueden desempeñar funciones clave en la comunicación intercelular. Arthrobacter sp. UMCV2 es una actinobacteria que promueve el crecimiento vegetal por la emisión del compuesto orgánico volátil N, N-dimetilhexadecilamina (DMHDA). Este compuesto estimula la adquisición de hierro, respuestas de defensa en plantas, y motilidad swarming en Arthrobacter sp. UMCV2. En este estudio, el borrador del genoma de esta bacteria fue ensamblado y comparado con los genomas de cepas tipo del género Arthrobacter, encontrando que no pertenece a ninguna de las especies descritas anteriormente. Exploraciones del genoma también revelaron la presencia de 16 genes relacionados a luxR, pero no se descubrieron homólogos luxI. Once de estas secuencias poseen el dominio de unión a DNA característico LuxR con un motivo hélice-giro-hélice y fueron designados como reguladores relacionados con autoinductores (AirR). Cuatro secuencias poseían dominios análogos LuxR y fueron designados como reguladores análogos a autoinductores (AiaR). Cuando la motilidad swarming fue inducida con DMHDA, ocho genes airR y dos genes aiaR aumentaron su expresión. Estos resultados indican que la expresión de múltiples genes relacionados con luxR se induce en actinobacterias, tales como Arthrobacter sp. UMCV2, por la acción del biocompuesto bacteriano DMHDA cuando se produce el comportamiento QS.
Instituto de Investigaciones Químico Biológicas. Doctorado en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/2; IIQB-D-2023-1065; Actinobacteria; LuxR solos; Motilidad swarming; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16571